HAK ANAK BEBAS BULLYING DI LINGKUNGAN SEKOLAH - Rosalina, Maria; Lestari, Dina; Meidira, Helfida; Rahmah, Rahmah (Universitas Islam Sumatear Utara, 2024)
Children have the right to receive education in a school environment that is safe, comfortable, and free from all forms of violence. In reality, however, bullying occurs in schools. The presence of bullying indicates that not all schools are capable of providing a safe and comfortable place for children to learn. Legally, bullying is a form of violence, as stated in Article 6 of the Ministry of Education and Culture Regulation No. 46 of 2023. Bullying in schools has negative effects on students, including victims, perpetrators, and bystanders. These effects may include a decline in self-confidence, mental health issues such as anxiety and depression, poor academic performance, feelings of isolation, and the risk of self-harm or suicide. Due to the negative impact of bullying on students' psychological, emotional, academic, and developmental well-being, the Legal Outreach Team from the Faculty of Law at UISU believes it is necessary to conduct legal outreach at SMK Nur Azizi Tanjung Morawa, Deli Serdang. The result was that the students gained knowledge about bullying, but they were still unaware of its legal consequences, the legal process for handling both the perpetrators and victims of bullying, and the negative aspects of bullying.